Strategy for the Implementation of Health Protocols on Mass Circumcision during a Pandemic in East Jakarta, Indonesia - Supartono, Basuki; Utari, Dyah; Kusumaningsih, Prita; Kaurow, Sarah Primadani; Zahra, Dewi Fatimah (Bangladesh Journal of Medical Science, 2023)
Background: Circumcision, a religious obligation for Male Muslims in Indonesia, is conducted at a high cost using health facilities. Meanwhile, while wanting to circumcise their children the pandemic situation reduces the economic capacity of the people. Therefore, it is necessary to conduct community service activities in the form of free circumcision performed en masse to help the poor. However, due to the coronavirus pandemic which has spread rapidly since the beginning of 2020, it is necessary to adhere to health protocols. Mass circumcision during a pandemic requires a health protocol strategy to ensure that activities are performed in a safe, comfortable, and satisfying state. East Jakarta has 2,937,859 people, with 486,110 people being children of age 0-19 years. The majority of residents in this city, about 96%, are Muslims. Meanwhile 3% percent of them, or 91,610 people, are considered poor. There is still a high need for the people of East Jakarta to conduct circumcision for their children during the pandemic, even though there is a decrease in their income. Methods: A free, safe, and comfortable mass circumcision is required with the implementation of health protocols. Out of 170 participants registered for the circumcision, 163 of them passed the Covid-19 screening, while two did not fulfill the indications for circumcision; hence only 161 children were circumcised using the smart clamp. Furthermore, the youngest, oldest, and most circumcised participants were 1, 15, and 5 – 9 years old (60 %), respectively. Results: The commonly used smart clamps were 13 in numbers, and the average circumcision time for each participant was 6 minutes. Furthermore, there were mild complications among 7 participants (4%). The participants’ parents were satisfied and advised their relatives to partake in mass circumcision in the future. Conclusion: Meanwhile, there were no reports of participants, parents, health workers, and committee members being infected with the coronavirus after completing the activity. The health protocol implementation strategy was successfully conducted during the free mass circumcision in East Jakarta, which took place safely, comfortably, and satisfactorily. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 785-796